2014
DOI: 10.1038/nature13323
|View full text |Cite
|
Sign up to set email alerts
|

Aryl hydrocarbon receptor control of a disease tolerance defence pathway

Abstract: Summary Disease tolerance is the ability of the host to reduce the impact of infection on host fitness. Analysis of disease tolerance pathways could provide new approaches for treating infections and other inflammatory diseases. Typically, an initial exposure to bacterial lipopolysaccharide (LPS) induces a state of refractoriness to further LPS challenge (“endotoxin tolerance”). We found that a first exposure to LPS activated the ligand-operated transcription factor aryl hydrocarbon receptor (AhR) and the hepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
596
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 595 publications
(629 citation statements)
references
References 50 publications
14
596
2
Order By: Relevance
“…This is not specific to TLR4, occurring downstream of other PRRs 125 and other sensors 18 . In some instances this response, coined as "trained immunity" 126 , has been functionally linked to the induction of disease tolerance 18 .…”
Section: Box 1: Tolerance and Disease Tolerancementioning
confidence: 86%
See 3 more Smart Citations
“…This is not specific to TLR4, occurring downstream of other PRRs 125 and other sensors 18 . In some instances this response, coined as "trained immunity" 126 , has been functionally linked to the induction of disease tolerance 18 .…”
Section: Box 1: Tolerance and Disease Tolerancementioning
confidence: 86%
“…These cytokines include IL-1α, IL-18 and IL-33, which polarize macrophages towards tissue healing regenerative responses, and as discussed in the previous section, contribute to the establishment of disease tolerance to infection (Figure 3a). Signaling via the aryl hydrocarbon receptor (AhR) a ligand-dependent transcription factor that senses exogenous environmental toxins and endogenous ligands, can also polarize macrophages towards the establishment of disease tolerance to bacterial infections 18 .…”
Section: Macrophagesmentioning
confidence: 99%
See 2 more Smart Citations
“…Results from a variety of laboratories over the past decade have revealed that the AHR has key roles in the development of cardiovascular, reproductive, and neural systems as well as in hematopoiesis and regulation of immune responses (Benedict, Lin, Loeffler, Peterson, & Flaws, 2000; Esser & Rannug, 2015; Gasiewicz, Singh, & Bennett, 2014; Kimura, Ding, & Tohyama, 2016; Lahvis et al., 2005; Quintana & Sherr, 2013; Singh et al., 2014; Stockinger, Di Meglio, Gialitakis, & Duarte, 2014). Some of these functions may involve natural or endogenous ligands such as metabolites generated by the microbiome, tryptophan metabolites, or lipid‐derived molecules (Bessede et al., 2014; Hubbard, Murray, & Perdew, 2015; McMillan & Bradfield, 2007; Moura‐Alves et al., 2014). The exact relationship between the AHR‐dependent toxicity of DLCs and PAHs and these physiological roles of AHR is not yet clear.…”
Section: Ahr Pathwaymentioning
confidence: 99%